Nurturing care: perceptions and practices of caregivers for children under five in the Ecuadorian highlands – a qualitative study - Tello, Betzabé; Mendoza-Gordillo, Maria J.; Moreano, Marcelo; Bates, Benjamin R.; Quinn, Katherine; Rogel, Camila; Grijalva, Mario J. (Frontiers in Public Health, 2024)
IntroductionThe importance of nurturing care for child development is well-established, and parents play a central role in providing this care. However, cultural values and traditions can influence child-rearing practices, and there are gaps in child welfare in Ecuador. Two research questions delve into caregivers’ definitions of nurturing care for children aged 0–5 and its alignment with World Health Organization’s concept.MethodsA qualitative methodology was applied to comprehensively explore caregivers’ perspectives and application of nurturing care across diverse cultural contexts in rural areas of Cotopaxi and Loja in Ecuador. Using snowball sampling primary caregivers, healthcare professionals, childcare workers, and community leaders were interviewed and participated in focus groups, examining its congruence with WHO’s Nurturing Care Framework for Early Childhood Development.ResultsWhile there is alignment with the WHO framework, the study reveals challenges such as a lack of awareness of the term “nurturing care” among participants. Findings also indicate issues in health communication, reliance on traditional medicine, and myths around nutritional practices. The role of technology in early learning is explored, noting both its advantages and disadvantages. Notably, preventive health activities were not mentioned, emphasizing a universal need for knowledge.ConclusionThis study urges tailored interventions for nurturing care, emphasizing success tied to robust healthcare and child protection. Urgency lies in cultural sensitivity, local adaptation, and targeted training for implementation. These insights contribute significantly to the global discourse, stressing the importance of context-specific approaches. Implications are crucial for policymakers, practitioners, and researchers dedicated to elevating care quality for vulnerable populations worldwide.